2008
DOI: 10.1523/jneurosci.2735-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

How Secure IsIn VivoSynaptic Transmission at the Calyx of Held?

Abstract: The medial nucleus of the trapezoid body (MNTB) receives excitatory input from giant presynaptic terminals, the calyces of Held. The MNTB functions as a sign inverter giving inhibitory input to the lateral and medial superior olive, where its input is important in the generation of binaural sensitivity to cues for sound localization. Extracellular recordings from MNTB neurons show complex spikes consisting of a prepotential, thought to reflect synaptic activation, followed by a postsynaptic action potential. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 34 publications
13
73
0
Order By: Relevance
“…Kopp-Scheinpflug et al (2002) also used waveform analysis to discriminate between presynaptic and postsynaptic events. Although their analysis may have started from an incorrect interpretation of complex waveforms (McLaughlin et al, 2008;Typlt et al, 2010) and did not consider spike depression or stochastic failures, many of our findings agree with theirs, including the delayed onset of inhibition. This delayed onset may appear surprising, given the proximity of the possible anatomical sources (Wickesberg and Oertel, 1990;Zhang and Oertel, 1993), but the slow time course of IPSPs in SBCs measured in vivo (Paolini and Clark, 1998) and our model simulations suggest that the delayed effect of inhibition originates from a gradual summation of inhibitory conductance.…”
Section: Mechanisms Of Inhibitionsupporting
confidence: 86%
“…Kopp-Scheinpflug et al (2002) also used waveform analysis to discriminate between presynaptic and postsynaptic events. Although their analysis may have started from an incorrect interpretation of complex waveforms (McLaughlin et al, 2008;Typlt et al, 2010) and did not consider spike depression or stochastic failures, many of our findings agree with theirs, including the delayed onset of inhibition. This delayed onset may appear surprising, given the proximity of the possible anatomical sources (Wickesberg and Oertel, 1990;Zhang and Oertel, 1993), but the slow time course of IPSPs in SBCs measured in vivo (Paolini and Clark, 1998) and our model simulations suggest that the delayed effect of inhibition originates from a gradual summation of inhibitory conductance.…”
Section: Mechanisms Of Inhibitionsupporting
confidence: 86%
“…Recent in vivo studies in young adult mice (ϳP32) and adult cats reported an activity-dependent decrease of A Post at very short ISIs (Mc Laughlin et al, 2008: AP depression for ISI Ͻ 20 ms; Lorteije et al, 2009: AP depression for ISI Ͻ 10 ms). We found a similar effect, which was strongly pronounced during early postnatal development (consistent with the Fig.…”
Section: Preceding Activity Predicts Variations In Postsynaptic Ap Ammentioning
confidence: 99%
“…The properties of spiking have been shown to depend on previous activity (Fedchyshyn and Wang, 2007;Mc Laughlin et al, 2008;Lorteije et al, 2009;Tolnai et al, 2009). Usually, the last interspike interval (ISI) is used as the independent variable.…”
Section: Failures Of Ap Transmissionmentioning
confidence: 99%
“…Because of its ability to fire at extraordinarily high rates (Schneggenburger and Forsythe, 2006), a predominant view is that the mature calyx of Held-MNTB synapse is a fail-safe relay (Mc Laughlin et al, 2008;Englitz et al, 2009). However, some studies show that this synapse fails under predepressed conditions as a result of spontaneous activity (Hermann et al, 2007), when decreases in postsynaptic excitability occur (Lorteije et al, 2009) or during high-frequency electrical or acoustic stimulation (Guinan and Li, 1990;Lorteije and Borst, 2011).…”
Section: Introductionmentioning
confidence: 99%